Feasibility and efficacy of gonadotropin-releasing hormone agonists for the prevention of chemotherapy-induced ovarian insufficiency in patients with malignant ovarian germ cell tumours (KGOG 3048R). (July 2020) - Choi, Min C.; Chung, Young S.; Lee, Jeong-Won; Kwon, Byung S.; Park, Byung K.; Kim, Se I.; Shim, Seung-Hyuk; Lee, Kwang-Beom; Seong, Seok J.; Lee, Sung J.; Lee, San H.; Yoo, Heon-Jong; et al.
Abstract: Background: This study assessed the effects of gonadotropin-releasing hormone agonists (GnRHa) on the prevention of chemotherapy-induced ovarian insufficiency among young patients with malignant ovarian germ cell tumour (MOGCT) receiving chemotherapy. Methods: This multicentre, retrospective study was conducted at 15 sites affiliated with the Korean Gynecologic Oncology Group and enrolled 354 patients between January 1995 and September 2018. Among them, 227 patients were included in this study and divided into two groups according to the use of GnRHa during chemotherapy (GnRHa versus no GnRHa groups). The primary objective was to compare the rates of menstrual resumption between the two groups. We also assessed the clinical determinants affecting menstrual resumption among the study groups. Results: There were no significant differences between the GnRHa (n = 63) and no GnRHa (n = 164) groups regarding age at diagnosis, parity, ethnicity, age at menarche, body mass index, International Federation of Gynecology and Obstetrics stage, mode of surgery and surgery type. The rate of menstrual resumption after chemotherapy was 100% (63 of 63) in the GnRHa group and 90.9% (149 of 164) in the no GnRHa group (p = 0.013). The mean periods from last chemotherapy to menstrual resumption were 7.4 and 7.3 months in the GnRHa and no GnRHa groups, respectively. GnRHa co-administration during chemotherapy reduced the likelihood of amenorrhoea after chemotherapy, although statistical significance was not confirmed in the univariate analysis (odds ratio: 0.276; 95% confidence interval, 0.004–1.317; p = 0.077). Conclusion: Temporary ovarian suppression with GnRHa during chemotherapy does not significantly increase the chances of menstrual resumption in young patients with MOGCT. Highlights: GnRH analogues appear to increase non-significantly the chances of menstrual recovery. The average time to menstrual recovery is unaffected by GnRH analogues.